Osmanlı İmparatorluğu'nda Istabl-ı Âmire Teşkilâtı (XV-XVI. yüzyıllar) - Karahan, Ayşe (My University, 2024)
Giriş ve üç bölümden müteşekkil bu çalışmada, Osmanlı saray teşkîlatı birimlerinden olan Istabl-ı Âmire’nin XV-XVI. yüzyıllardaki teşkilât yapısı incelenmiştir. Giriş’te, öncelikle Osmanlı Devleti’nden önce hüküm süren Türk-İslam devletlerinin ana hatlarıyla Istabl teşkilâtları hakkında bilgi verilmiştir. Daha sonra çalışmada kullanılan ana kaynakların muhtevası tanıtılarak konu ile ilgili mevcut literatür hakkında bir değerlendirme yapılmıştır. Birinci bölümde, Istabl-ı Âmire’nin kuruluşu ve gelişimi, incelenen dönem içerisindeki personelinin mevcudu, maaşları ve terfileri izah edilmiştir. Bunun yanı sıra Istabl-ı Âmire’nin gelirleri; koru, çayır ve kışlakları; taşrada teşkilâta bağlı olarak görev yapan voynukları; hayvan, yem ve malzeme temini ile bunların ilgililere dağıtımı birinci bölümde üzerinde durulan diğer hususlardır. İkinci bölümde, Istabl-ı Âmire teşkilâtının büyük mîrâhûr tarafından yönetilen Büyük Âhûr kısmındaki birimleri ve görevlileri hakkında malûmat verilmiştir. Üçüncü bölümde de, Istabl-ı Âmire teşkilâtının küçük mîrâhûrun idareciliğini yaptığı Küçük Âhûr kısmındaki birimleri ve görevlileri izah edilmiştir.

In this study consisting of an introduction and three chapters, organizational structure of Istabl-ı Âmire, one of the units of the Ottoman palace organization, in the 15th-16th centuries was examined. In the introduction, information is given about the Istabl organizations of the Turkish-Islamic states that ruled before the Ottoman Empire. Then, the content of the main sources used in the study was introduced and an evaluation was made about the existing literature on the subject. In the first chapter, the establishment and development of Istabl-ı Âmire, the number of its personnel, their salaries and promotions during the examined period are explained. In addition, the revenues of Istabl-ı mire; groves, meadows and winter quarters; voynuks serving under the organization in the provinces; The supply of animals, feed and materials and their distribution to those concerned are other issues emphasized in the first section. In the second chapter, information is given about the units and officials of the Istabl-ı Âmire organization in the Great Barn section, which is managed by the Master of Great Stable. In the third chapter, the units and officials of the Istabl-ı Âmire organization in the Lesser Stable section, managed by the Master of the Lesser Stable, are explained.
Keywords: Courts and courtiers; History; Istabl-ı Âmire; Master of the Great Stable; Master of the Lesser Stable; Mîrâhûr-ı Evvel; Mîrâhûr-ı Sânî; Osmanlı Devleti, 1288-1918; Osmanlı Sarayı The Royal Stables; Ottoman Empire, 1288-1918; Ottoman Palace; Saray ve saray mensupları; Tarih; Turkey; Türkiye